Bovine Lung Insufflation as a Dynamic Model for Teaching Respiratory Anatomy and Physiology: A Comparative Educational Approach - Pira, Orozco; Johanna, Wendy; Rigoberto, Villa - Ramírez (Journal of Educational Research and Policies, 2026)
The insufflation technique as a method to preserve and study the morphology of bovine lung models. This study aimed to evaluate the insufflation technique as a preservation method in the morphological study of bovine lung models, describing their anatomical and functional characteristics. Fresh bovine lungs were used and subjected to controlled insufflation to observe structural changes in the lobes, bronchi, and alveoli. The results demonstrated considerable distensibility of the bovine lungs, allowing homogeneous expansion of the lobes and clear differentiation of anatomical structures, such as interlobar fissures and main airways. The lobes showed significant expansion without evidence of collapse or tissue damage, enabling detailed observation of the internal lung architecture. These findings underscore the utility of bovine lung models in morphological studies, providing valuable information on the structure and behavior of lung tissues under controlled insufflation. The insufflation technique as a method to preserve and study the morphology of bovine lung models.